Pendampingan UMKM untuk Meningkatkan Omset Penjualan di Era Digital pada UMKM Keripik Singkong di Desa Wanajaya Kecamatan Cibitung - Melani Putri; Etty Zuliawati Zed; Vanessa Dwie Meimita; Ulan Ulan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
MSMEs play an important role in the local and national economy. However, many MSMEs still face challenges in utilizing digital technology to increase sales turnover. This article reports the results of assistance activities for cassava chips MSMEs in Wanajaya Village, Cibitung District, with the aim of helping business actors utilize digital technology to market their products more widely. The methods used are socialization, training and evaluation of the use of digital platforms such as marketplaces, social media and digital marketing techniques. The results show an increase in the knowledge and skills of MSME players in digital marketing which has a direct impact on increasing sales turnover by up to 30% in the three months after the intervention.